Pediatric ovarian angiosarcoma treated with systemic chemotherapy and cytoreductive surgery with heated intraperitoneal chemotherapy: Case report and review of therapy. Issue 7 (11th April 2019) - Pariury, Holly; Golden, Carla; Huh, Winston W.; Cham, Elaine; Chung, Taylor; Hayes‐Jordan, Andrea
Abstract: Ovarian angiosarcoma is a rare and aggressive vascular tumor, which has a 5‐year overall survival of less than 30% for patients with nonmetastatic disease and almost certain death within 1 year for those with metastasis. Here, we briefly review historical approaches to therapy and present a long‐term survivor in the case of an 11‐year‐old female with metastatic ovarian angiosarcoma. This is the second reported case to utilize heated intraperitoneal chemotherapy in the treatment of this disease. Our patient is currently alive and well 3 years after initial diagnosis, significantly longer than any reported case of advanced‐stage ovarian angiosarcoma.